2016
DOI: 10.1002/ls.1332
|View full text |Cite
|
Sign up to set email alerts
|

Thickness and scratch resistance of adsorbed film formed by triblock symmetrical copolymer solutions

Abstract: The thickness and scratch resistance of adsorbed films formed on mild steel samples (MS1020), which have been immersed in water copolymer solutions, are reported. The effects of bulk temperature and the copolymer structures, normal, poly(ethylene oxide)m‐poly(propylene oxide)n‐poly(ethylene oxide)m, and reverse, poly(propylene oxide)n‐poly(ethylene oxide)m‐poly(propylene oxide)n, are elucidated. The films' thicknesses are independent of structure but not of temperature. The adsorbed films of above cloud point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Additionally, this theoretical investigation also aims to support previous experimental studies [1,15,19,20,35]. An MD model has been developed to simulate realistically the self-assembled molecular structure of adsorbed Pluronics at the atomic scale.…”
Section: Introductionmentioning
confidence: 72%
“…Additionally, this theoretical investigation also aims to support previous experimental studies [1,15,19,20,35]. An MD model has been developed to simulate realistically the self-assembled molecular structure of adsorbed Pluronics at the atomic scale.…”
Section: Introductionmentioning
confidence: 72%
“…It is clearly demonstrated that the adsorbed copolymer layer can be removed from the surface by means of a simple surface cleaning process ( Figure 13 left) while those lubricated by the VO/W emulsions still have residue on the surface (Figure 13 right). While vegetable oils tendency to produce ROOH hydroperoxide through oxidation results in thickening, varnish formation and sludge deposition on surfaces [26,63] and postulates poor cleanability, triblock copolymers have high wetting and spreading ability, thus are easily rinsed with Milli-Q water [8,20]. This direct observation, together with the QCM film removal of Figures 3 and 4 at rinsing stage (above 20 min) demonstrates the superior surface cleanability of the copolymer solutions compared to the VO/W emulsions, albeit with higher friction and wear.…”
Section: Worn Track and Ball Scar Analysismentioning
confidence: 99%
“…This makes vegetable oil in water emulsion a cost effective green and renewable lubricant with low oil consumption, in accordance with the minimum quantity lubricant MQL strategy [18,19]. Aqueous triblock copolymer solutions are another class of low cost aqueous alternatives, possessing comparable tribological performance to conventional lubricants and excellent surface cleanability [8,20,21]. …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…A standard stainless steel (SS) and TiO 2 -coated SS surfaces, which are partly hydrophobic, 7,8 were chosen in recent experimental studies. 6,8,10,11 In a theoretical approach using molecular dynamics (MD) simulations, nascent iron and pure titanium oxide surfaces were used to relate to the experimental findings on these surfaces.…”
Section: Introductionmentioning
confidence: 99%